TRENDS OF HAJJ AND UMRAH ON INSTAGRAM: COMMERCIALIZATION AND SELF-REPRESENTATION - Mawardi, Imam; Huda, Ahmad Faisal; Risqiyah, Lailatul (Institut Agama Islam Negeri Metro, 2024)
This article discusses the trend of Hajj and Umrah on Instagram, which is a form of expression of pilgrims on social media. The phenomenon is represented through the hajj hastag (#haji) and umrah hastag (#umrah). This research uses qualitative research methods, with a virtual ethnography approach. Data were collected through posts and comments on Instagram with #hajj and #umrah, and from literature studies. The data was then analyzed using critical discourse analysis theory. That every discourse is constructed from the identity, background, and purpose of the discourse. It was found that the expressions of Hajj and Umrah pilgrims on social media were represented with a variety of expressions and purposes. First, there are many trends in the phenomenon of Hajj and Umrah on Instagram. It is used as a means of personal and group promotion, such as travel agencies, food, and Hajj souvenirs. Second, a person's post when performing Hajj or Umrah is a form of self-expression and expression of gratitude so that social media is used to share their experiences as a form of gratitude and in order to motivate others.